The intimacy of paper in early and nineteenth-century American literature - Senchyne, Jonathan (University of Massachusetts Press, 2020)
Abstract:
Chapter 1: Paper Publics and Material Textual Affiliations in American Print Culture – Chapter 2: The Gender of Rag Paper in Anne Bradstreet and Lydia Sigourney – Chapter 3: The Ineffable Socialities of Rags in Henry David Thoreau and Herman Melville – Chapter 4: The Whiteness of the Page: Racial Legibility and Authenticity
Keywords: American literature / History and criticism; Paper in literature; Papermaking / United States / History; Books / Social aspects / History; Printing / Social aspects / History; Paper industry / Social aspects / History; Literatur; Papier; Buchdruck; Papierindustrie